Apoptotic Induction in Human Cancer Cell Lines by Antimicrobial Compounds from Antarctic Streptomyces fildesensis (INACH3013) - David Astudillo-Barraza; Romulo Oses; Carlos Henríquez-Castillo; Clemente Michael Vui Ling Wong; José M. Pérez-Donoso; Cristina Purcarea; Heidge Fukumasu; Natalia Fierro-Vásquez; Pablo A. Pérez; Paris Lavin (Fermentation, 2023)
The Antarctic Streptomyces fildesensis has been recognized for its production of antimicrobial compounds with interesting biological activities against foodborne bacteria and multi-resistant strains, but not for its potential antiproliferative activity and mechanisms involved. Two bioactive ethyl acetate extract (EAE) fractions were purified via thin-layer chromatography and High-Performance Liquid Chromatography (HPLC), showing that orange-colored compounds displayed antimicrobial activity against pathogenic bacteria even after shock thermal treatment. The UV–VIS features of the active compounds, the TLC assay with actinomycin-D pure standard, Fourier transform infrared (FTIR) spectra and the ANTISMASH analysis support the presence of actinomycin-like compounds. We demonstrated that S. fildesensis displays antiproliferative activity against human tumor cell lines, including human breast cancer (MCF-7), prostate cancer (PC-3), colon cancer (HT-29) and non-tumoral colon epithelial cells (CoN). The half-maximal effective concentrations (EC50) ranged from 3.98 µg/mL to 0.1 µg/mL. Our results reveal that actinomycin-like compounds of S. fildesensis induced apoptosis mediated by caspase activation, decreasing the mitochondrial membrane potential and altering the cell morphology in all tumoral and non-tumoral cell lines analyzed. These findings confirm the potential of the psychrotolerant Antarctic S. fildesensis species as a promising source for obtaining potential novel anticancer compounds.